Evaluation of an enhanced behavioural monitoring system in UK open prisons - Goodley, Gary (Criminology & criminal justice, 2025)
Behavioural monitoring has efficacy in predicting recidivism. As an intervention however, the proven effectiveness is limited. This study is an evaluation of the Enhanced Behaviour Monitoring scheme operating across open prisons in England and Wales, to reduce instances of failure (e.g. abscond, re-offending). Utilising a matched sample design, logistic regression analyses showed Enhanced Behaviour Monitoring had null effects on serious recidivistic outcomes (e.g. abscond, reoffending). Those allocated to Enhanced Behaviour Monitoring were more likely to get recalled before completing the intervention. In essence, Enhanced Behaviour Monitoring was utilised primarily as a surveillance programme – to defend against risk exposure – resulting in recalls to closed prisons misaligned to the community recidivism risk; undermining the open prison concept. We discuss the findings in the context of the adverse effects of ‘surveillance only’ community supervision programmes. We argue for developing the rehabilitative potential within Enhanced Behaviour Monitoring and mitigating against excessive risk exposure through systems level policy change.